Evaluasi dan Perbaikan Antarmuka Pengguna Situs Web Otoritas Kompeten Badan Karantina Ikan, Pengendalian Mutu dan Keamanan Hasil Perikanan (BKIPM) dengan menggunakan Metode Goal-Directed Design (GDD) - Nabila Rahmah; Retno Indah Rokhmawati; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Fish Quarantine, Quality Control and Safety of Fishery Products has a website called the Competent Authority which needs improvement in terms of incorrect interface appearance and information layout. This study aims to produce a new website user interface improvement design using the five phases contained in the Goal-Directed Design method. In the research phase, an initial evaluation of website users was carried out by interviewing and filling in a Post-Study-System Usability Questionnaire (PSSUQ) to get input on improvements to be made. In the modeling phase, produce personas, user journey retrospectives and prospects to get an overview of users and interactions of the system. The requirements phase produces the scenario context and the functional requirements of the system. In the framework phase, produce a user interface framework based on input and functional requirements. The refinement phase produces a high-fidelity prototype and final evaluation using usability testing. After each phase has been completed, a design comparison will be made before and after the repair is made. The final results of this study get good input from users because overall users find it easy to use this website and can meet their needs. The website gets a score of 1.95 on the overall scale of the PSSUQ questionnaire which means that usability in the repair design is high and users are satisfied.